2017
DOI: 10.1186/s13195-017-0300-8
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of sex on the impact of diagnosis and amyloid positivity on verbal memory and hippocampal volume

Abstract: BackgroundAlzheimer’s disease (AD) impacts men and women differently, but the effect of sex on predementia stages is unclear. The objective of this study was to examine whether sex moderates the impact of florbetapir positron emission tomography (PET) amyloid positivity (A+) on verbal learning and memory performance and hippocampal volume (HV) in normal cognition (NC) and early mild cognitive impairment (eMCI).MethodsSeven hundred forty-two participants with NC and participants with eMCI from the Alzheimer’s D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 49 publications
(56 reference statements)
2
37
0
Order By: Relevance
“…In recent years, MRI-based biomarkers of AD that target gray matter atrophy or shape were found to be the most commonly used measures ( Risacher et al, 2009 ; Ezzati et al, 2016 ; Caldwell et al, 2017 ). Reduced hippocampal volume has been well studied in AD and MCI individuals (for a review, see Shi et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, MRI-based biomarkers of AD that target gray matter atrophy or shape were found to be the most commonly used measures ( Risacher et al, 2009 ; Ezzati et al, 2016 ; Caldwell et al, 2017 ). Reduced hippocampal volume has been well studied in AD and MCI individuals (for a review, see Shi et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in MCI patients with a higher risk to develop AD, women were found to show greater cognitive decline and more total tau, Aβ-42 ratios that were exacerbated by the presence of the apolipoprotein e4 allele [60]. Furthermore, studies suggest that women are more likely to show associations of progression to AD with changes in hippocampal volume and amyloid burden, while in men white matter hyperintensities are more related to disease progression [59,61,62]. This work is an important step to determine whether sex differences can aid in our understanding of disease progression and possible treatment strategies that may need to differ by sex.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond cognitive reserve, recent research by our group suggests women may have neural reserve in the face of early AD pathology as indicated by biomarkers. Specifically, we have demonstrated that women— and not men— with A+ and normal cognition (NC) show right hippocampal volumes comparable to women with NC and a negative florbetapir PET study (A–); however, this sex-specific advantage is lost in early mild cognitive impairment (eMCI) [ 12 ]. Mechanisms of this proposed sex-based hippocampal reserve remain unclear, but may include a complex host of interactive factors including lifetime neuroprotective effects of estrogen [ 13, 14 ], and sex differences in genetic [ 5, 15 ], inflammatory [ 16 ], metabolic [ 17 ], and psychosocial factors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%